PENGARUH PROFITABILITAS, LIKUIDITAS, SOLVABILITAS DAN GOOD CORPORATE GOVERNANCE TERHADAP PERINGKAT OBLIGASI - Reyvina Yuandani Putri; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis study aims to find out how the influence of Profitability, Liquidity and Good Corporate Governance on Bond Rankings in banking companies listed on the Stock Exchange for the period 2016-2018. The population in the study were banking companies listed on the IDX, which numbered 14 banking companies which were taken using purposive sampling technique, namely the selection of samples according to certain criteria. The data collection method used is the documentation method, namely by studying and using annual reports obtained from the IDX. The data analysis technique used in this study is multiple linear regression, classic assumption test. The results of the study prove that partially profitability variables have a positive effect on bond ratings, while the variables of liquidity, solvability, managerial ownership, institutional ownership, board of commissioners and audit committees do not significantly influence bond ratings. Simultaneously profitability, liquidity, solvency, managerial ownership, institutional ownership, board of commissioners, audit committees jointly have a significant effect on bond ratings.Keywords: Profitability, Liquidity, Solvability, Managerial Ownership, Institutional Ownership, Board of Commissioners, Audit Committee